Renewable energy and AI for sustainable development / edited by Sailesh Iyer, Anand Nayyar, Mohd Naved, Fadi Al-Turjman. - Iyer, Sailesh (Sailesh Suryanarayan), 1973-; Nayyar, Anand; Naved, Mohd; Al-Turjman, Fadi (CRC Press, 2023)
"This book aims at contributing to the increasing interest in reducing the environmental impact of energy as well as its further development and will act as a strong reference to Engineers, Architects, Technicians interested in and working with energy systems, scientists and engineers in the underdeveloped/developing countries, Industries, Manufacturers, Inventors, Universities, Researchers and Consultants to understand the foundation to advanced concepts and Research trends in the domain of Renewable Energy and Sustainable Computing. The content coverage of the Book organized in the form of 11 simple, lucid and exhaustive Chapters providing an exhaustive view of global renewable energy scenario and how Science and Technology can play a vital role in Renewable Energy"-- Provided by publisher.
Keywords: Renewable energy sources.; Clean energy.; Electronic waste.; Sustainability -- Technological innovations.